2024
DOI: 10.1097/bot.0000000000002763
|View full text |Cite
|
Sign up to set email alerts
|

Use of 3D-Printed Implants in Complex Foot and Ankle Reconstruction

Matthew Brown,
Gerard Cush,
Samuel B. Adams

Abstract: Summary: Treatment of traumatic critical-sized bone defects remains a challenge for orthopaedic surgeons. Autograft remains the gold standard to address bone loss, but for larger defects, different strategies must be used. The use of 3D-printed implants to address lower extremity trauma and bone loss is discussed with current techniques including bone transport, Masquelet, osteomyocutaneous flaps, and massive allografts. Considerations and future directions of implant design, augmentation, and optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…After that, with the advancement of materials science, the medical field began to experiment with using biocompatible materials for 3D printing to manufacture medical devices and implants suitable for implantation in the human body, as well as for drug preparation. , This includes implants for bone repair, prosthetics, stents and artificial organs. , Nowadays (2010s to present), with the advancement of 3D printing technology, customized medical devices have become widely used in the medical field. Physicians can customize surgical instruments, implants, braces, and orthodontic devices based on the individual anatomical features of patients to improve surgical outcomes and patient comfort. , Meanwhile, in recent years, bioprinting is a cutting-edge technology in the medical field that uses biological materials and cells to manufacture tissues and organs layer by layer. , Additionally, there are emerging applications that involve creating 3D-printed models for investigating tumor biological behavior. , While bioprinting is still in the research stage, it has shown potential applications in regenerative medicine, tissue engineering, and organ transplantation. In summary, Figure briefly summarizes the major breakthroughs in the application of 3D printing in the medical field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After that, with the advancement of materials science, the medical field began to experiment with using biocompatible materials for 3D printing to manufacture medical devices and implants suitable for implantation in the human body, as well as for drug preparation. , This includes implants for bone repair, prosthetics, stents and artificial organs. , Nowadays (2010s to present), with the advancement of 3D printing technology, customized medical devices have become widely used in the medical field. Physicians can customize surgical instruments, implants, braces, and orthodontic devices based on the individual anatomical features of patients to improve surgical outcomes and patient comfort. , Meanwhile, in recent years, bioprinting is a cutting-edge technology in the medical field that uses biological materials and cells to manufacture tissues and organs layer by layer. , Additionally, there are emerging applications that involve creating 3D-printed models for investigating tumor biological behavior. , While bioprinting is still in the research stage, it has shown potential applications in regenerative medicine, tissue engineering, and organ transplantation. In summary, Figure briefly summarizes the major breakthroughs in the application of 3D printing in the medical field.…”
Section: Introductionmentioning
confidence: 99%
“…Physicians can customize surgical instruments, implants, braces, and orthodontic devices based on the individual anatomical features of patients to improve surgical outcomes and patient comfort. 13,14 Meanwhile, in recent years, bioprinting is a cutting-edge technology in the medical field that uses biological materials and cells to manufacture tissues and organs layer by layer. 15,16 Additionally, there are emerging applications that involve creating 3D-printed models for investigating tumor biological behavior.…”
Section: ■ Introductionmentioning
confidence: 99%